2021
DOI: 10.1016/j.surg.2020.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Gender distribution among surgical journals’ editorial boards: Empowering women surgeon scientists

Abstract: Background: Gender disparities still exist in the field of academic surgery. Women face additional obstacles obtaining high-ranking, surgical academia positions compared to men, and this may extend to the appointment of editorial board members. We aim to evaluate the gender distribution of editorial board members, associate editors, and editors-in-chief of top US surgical journals and to recommend interventions, which can promote equitable gender representation among editorial boards. Methods: The study is a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 25 publications
4
31
0
Order By: Relevance
“…8 In addition, our findings on the increased proportion of women in female and pediatric urology are in keeping with the demographic data from the American Board of Urology. 8 This trend may be further explained by the availability of mentorship during residency .9 Among the women EB members, all but one were from high-income countries. This highlights an additional layer of disparity that exists among women EB members.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…8 In addition, our findings on the increased proportion of women in female and pediatric urology are in keeping with the demographic data from the American Board of Urology. 8 This trend may be further explained by the availability of mentorship during residency .9 Among the women EB members, all but one were from high-income countries. This highlights an additional layer of disparity that exists among women EB members.…”
Section: Discussionsupporting
confidence: 83%
“…6 Despite the percentage of women EB members almost doubling within five years, it remains lower than other specialties such as general surgery (18.3%) and plastic surgery (18.2%). 8 It is, however, higher than neurosurgery (8.3%) and orthopedic surgery (6.1%), two surgical subspecialties that are historically known to be predominantly male. 8 In addition, our findings on the increased proportion of women in female and pediatric urology are in keeping with the demographic data from the American Board of Urology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While temporal trend could not be examined, women were found to be a minority across editorial positions in transplantation journals regardless of quartile. Previous literature found that surgical journals had a lower mean proportion of women editorial board members and associate women editors at 18.3% and 20.1%, respectively [7]. Interestingly, women may be better represented in transplantation, a subspecialty under both medicine and surgery.…”
mentioning
confidence: 94%